Early fall and late winter diets of migratory caribou in northwest Alaska - Joly, Kyle; Cameron, Matthew D. (Rangifer, 2018)
Lichens are the primary winter forage for large herds of migratory caribou (Rangifer tarandus). Caribou select for lichens more than they are available across the landscape and they generally avoid, during winter, habitat that has been burned by wildfires for decades while lichen abundance recovers. However, the relative importance of lichens in the diet is subject to debate. From 2010-2013, we conducted one of the largest microhistological studies of the early fall (58 samples from 1 site) and late winter (338 samples from 58 sites) diets of barren-ground caribou. Lichens constituted 71% of the late winter diets of caribou in northwest Alaska, whereas moss (11%) and shrubs (9%) were the next most common forage items. Early fall diets were very similar to late winter, perhaps because deciduous vegetation is senescent during both periods. Diets of males, non-pregnant females and pregnant females were not significantly different. Pregnancy was not associated with the abundance of any forage type during winter but was associated with higher physiological stress. This result was expected as fall body condition dictates conception, caribou are ‘capital’ breeders, and gestation can be energetically demanding. Caribou that migrated south (i.e., wintered south of 67.1°N) had lower levels of nutritional stress, higher levels of lichen in the diet, and lower levels of moss and shrubs compared to caribou that did not migrate south. Future investigations into the potential connection between lichen abundance in the winter diet and survivorship, as well as linking the late summer diets of individuals to their reproductive success, should be undertaken.